THIP: A new TPRF-like fuel surrogate development approach to better match real fuel properties. (15th February 2021) - Gail, Sandro; Cracknell, Roger F.; Poulet, Benoit; Lovett, Guy; Festa, Andrea; Shankar, Varun; Büttgen, Rene D.; Heufer, Karl Alexander
Highlights: 3 component gasoline surrogates are usually made from toluene, isooctane and n - heptane. Gasoline surrogates with toluene, isopentane and n-heptane (THIP) are proposed. THIP surrogates capture RON/ MON and Ignition Delay (measured in RCM) of a real fuel. THIP surrogates are better able to represent a realistic DVPE and density. Chemical kinetic mechanisms exist to model THIP surrogates with reasonable accuracy. Abstract: Simple surrogate formulations for gasoline are useful for modelling purposes and for comparing experimental results using a carefully designed fuel. Simple three component surrogate fuels based on toluene, n-heptane and isooctane, called toluene primary reference fuels (TPRF), are frequently used to match the RON and MON of actual gasoline fuels. In this work the main advantages of using an alternative three-component surrogate formulation, based on toluene, n-heptane and isopentane (THIP) are presented. Given a reference gasoline, good representations of RON and MON are achieved as well as better matching density, distillation properties and other volatility parameters associated with the lighter end of gasoline fuels. In particular, THIP surrogates can replicate Dry Vapour Pressure Equivalent (DVPE) values ranging from 10.4 kPa to 138.9 kPa, fully covering the EN228 Summer and Winter gasoline specifications. Moreover, Rapid Compression Machine (RCM) results demonstrate that THIP surrogates can reproduce the essential characteristics of the reference gasoline in terms of ignition delay time versus temperature. An existing chemical kinetic mechanism is shown to be able represent THIP surrogate well.